2010
DOI: 10.1111/j.1582-4934.2009.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the progestagen‐associated endometrial protein gene in human melanoma

Abstract: Utilizing gene microarray profiling of melanoma samples, we have recently identified a novel gene overexpressed in both thick primary and metastatic melanomas. This gene, progestagen-associated endometrial protein (PAEP), has never before been implicated in the oncogenic processes of melanoma, with its true function in oncogenesis and tumour progression relatively unknown. Overexpression of the PAEP gene in freshly procured thick primary and metastatic melanoma samples (58%) and daughter cell lines (77%) is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
2
26
1
2
Order By: Relevance
“…Increasing glycodelin concentrations have been linked to deregulated PLAU and MMP9 activity and inhibition of trophoblast invasiveness (11). This finding is supported by observations in melanoma cells, where cell migration and invasion were strongly inhibited after glycodelin silencing (16). In our study, we observed the expression of glycodelin in metastatic lymph nodes and distant metastases.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Increasing glycodelin concentrations have been linked to deregulated PLAU and MMP9 activity and inhibition of trophoblast invasiveness (11). This finding is supported by observations in melanoma cells, where cell migration and invasion were strongly inhibited after glycodelin silencing (16). In our study, we observed the expression of glycodelin in metastatic lymph nodes and distant metastases.…”
Section: Discussionsupporting
confidence: 78%
“…Atypical glycodelin expression is observed in hormone-related breast cancer, endometrial cancer, and ovarian cancer (15). Recent studies have demonstrated glycodelin expression in melanoma cells and lung cancer (16,17). Geneexpression data from our group revealed that PAEP is expressed in a lung cancer cell line as well (18).…”
Section: )mentioning
confidence: 80%
“…Song et al (9) demonstrated that PAEP is also involved in neovascularization during tumor growth (9). However, our previous study presumed that PAEP is a tumor promoter in melanoma (10), suggesting contradictory results as compared to other studies.…”
Section: Introductioncontrasting
confidence: 44%
“…The gene has also been demonstrated to be differentially involved in certain tumor (18,19). Several studies have suggested that PAEP inhibits tumor cell growth and promotes cell differentiation as a tumor suppressive factor; however, other authors have demonstrated that PAEP increases the invasion of endometrial adenocarcinoma cells (20) and melanoma (10). Therefore, the function of PAEP gene expression in tumorigenesis and tumor progression remains unclear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation